Is disordered eating behavior more prevalent in adolescents with early‐onset type 1 diabetes than in their representative peers?. Issue 4 (22nd December 2013) - Baechle, Christina; Castillo, Katty; Straßburger, Klaus; Stahl‐Pehe, Anna; Meissner, Thomas; Holl, Reinhard W.; Giani, Guido; Rosenbauer, Joachim; ,
ABSTRACT Objective Despite modern therapeutic regimens, youths with Type 1 diabetes may be at increased risk of mental and behavioral disorders. In this study, the prevalence of disordered eating behavior (DEB) in intensely treated children and adolescents with early‐onset Type 1 diabetes and peers from the general population was compared. Method Data from 629 patients from a population‐based, nationwide survey (54.1% male, mean age 15.3 years) with early‐onset Type 1 diabetes of at least 10 years duration were compared with data from 6, 813 participants of the German KiGGS study (51.3% male, mean age 14.6 years). The generic SCOFF questionnaire was used as screening instrument to identify participants with symptoms of DEB. Both groups were compared with multivariable regression analysis adjusting for sociodemographic covariates. Results 31.2% of the female and 11.7% of the male diabetic patients and 28.9% of the females and 15.2% of the males in the comparison group were SCOFF‐positive (SCOFF score ≥2; p > .05). The odds for symptoms of eating disorders were 3.7% higher in female and 4.3% lower in male patients with diabetes than in the comparison group, but the differences were not significant. 20.5% of the female and 18.5% of the male diabetic patients reported insulin restriction at least three times per week. Discussion Children and adolescents with early‐onset Type 1 diabetes of long duration do not seem to be more frequently SCOFF‐positive than peers. However, as insulin restriction is practiced in a substantial portion of patients, attention for insulin restriction in diabetes care is essential. © 2013 Wiley Periodicals, Inc. (Int J Eat Disord 2014; 47:342–352)